Research on structural optimization method of FRP fishing vessel based on artificial bee colony algorithm. (July 2018) - Li, Kai; Yu, Yanyun; Wang, Yunlong; Hu, Zhenwu
Highlights: An ABCA-based structural optimization method of FRP fishing vessel is proposed. FEA modeling is simplified by using beam element to simulate top hat stiffener. Whole ship structure is considered for optimization. FEA is performed parametrically and repeatedly during optimization. Small amount of calculation with good convergence property. Abstract: Due to the increase of the operating cost and material cost, weight reduction has attracted much attention among ship designers and ship owners. Ship structure optimization remains a very complicated problem due to the feasible combinations of structural members with different sections are numerous. In the present work, based on artificial bee colony (ABC) algorithm, we propose a structural design optimization method of fiber reinforced plastic (FRP) ship structure. The objective of the proposed optimization method is to minimize the weight of FRP ship structure under a group of constraints. In order to deal with parametric finite element analysis (FEA) of the whole FRP ship structure, the modeling work is simplified by using beam element instead of shell element to simulate top hat stiffener. To evaluate the applicability of the proposed method, it was applied to a problem for finding optimal structure of a 32.98 m FRP fishing vessel. The result shows that the developed program can decrease the structural weight by about 8.31%. Thus, this study will be able to contribute to make energy saving and environment-friendly ship.